KEWENANGAN PT. PELABUHAN INDONESIA II (PERSERO) CABANG PANJANG DALAM PENGELOLAAN LAHAN KEPELABUHANAN (Study Pemisahan Regulator dan Operator Pelabuhan) - Aditiawan Muslim (Universitas Lampung, 2016)
The authority PT. Pelabuhan Indonesia II (Persero) Cabang Panjang in land management Ports after enactment Law Number 17 of 2008 on Shipping have experienced changes. Where the scope of portland management includes the formulation of Port Master Plan, the provision of portland, port monitoring land use, and exploitation of the portland. The results showed that the scope of authority land management port is a portland concession. it relates to the status of PT. Pelabuhan Indonesia II (Persero) Cabang Panjang as a Badan Usaha Pelabuhan(BUP) which has the function of a role as a port operator. As for the formulation of the Port Master Plan, the provision of portland, port monitoring land use under the authority of the Port Authority which has the function of a role as a regulator. In a land concession pass port, PT. Pelabuhan Indonesia II (Persero) Cabang Panjang is not included in the Port Enterprises whose business activities can run only after getting the concession of the port authority. Because granting concessions only to Port Business Entities are new. In addition, in article 344 paragraphs (2) of Law Number 17 of 2008 on Shipping provides legal certainty on the legal status of SOEs Ports presence in the business activities of port services. Keywords: Authority, the Port Authority, PT. Pelabuhan Indonesia II (Persero) Cabang Panjang